Multiple antenna relay-assisted schemes for the uplink OFDM based systems - Moço, A.
The aim of this paper is to propose and assess the performance of multiple antenna half-duplex relay-assisted cooperative schemes designed for the uplink OFDM based systems. We consider the use of an antenna array at the relay and base station and a single antenna at the mobile terminals. Two types of relay protocols are considered: equalize-and-forward and decode-and-forward. The performance of the proposed multiple antenna relay-assisted schemes is evaluated under realistic scenarios, considering typical pedestrian scenarios based on WiMAX specifications. The proposed schemes are also compared against the OFDM based non-cooperative systems. The goal is to identify the scenarios in which cooperating may be beneficial. Numerical results show that multiple antenna relay-assisted schemes outperform the non-cooperative ones in most of the studied scenarios.